2016
DOI: 10.1016/j.jmbbm.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans biofilm transient viscoelastic fluid behaviour during high-velocity microsprays

Abstract: Using high-speed imaging we assessed Streptococcus mutans biofilm-fluid interactions during exposure to a 60-ms microspray burst with a maximum exit velocity of 51m/s. S. mutans UA159 biofilms were grown for 72h on 10mm-length glass slides pre-conditioned with porcine gastric mucin. Biofilm stiffness was measured by performing uniaxial-compression tests. We developed an in-vitro interproximal model which allowed the parallel insertion of two biofilm-colonized slides separated by a distance of 1mm and enabled h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Recently, we had developed a microfluidic flow channel system for investigating rapid high velocity water and air microspray interactions with S. mutans biofilms for dental cleaning applications (Fabbri et al, 2015). HSC videography suggested the formation of migratory ripple-like structures at the biofilm/fluid interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we had developed a microfluidic flow channel system for investigating rapid high velocity water and air microspray interactions with S. mutans biofilms for dental cleaning applications (Fabbri et al, 2015). HSC videography suggested the formation of migratory ripple-like structures at the biofilm/fluid interface.…”
Section: Resultsmentioning
confidence: 99%
“…S. mutans biofilms have been widely used in research to investigate biofilm mechanical properties and detachment (Vinogradov et al, 2004;Cense et al, 2006). We previously performed high-speed camera (HSC) videography during the exposure of in vitro S. mutans interproximal dental biofilms to high-velocity (60 m/s) impacts from micro water jets and sprays using an interdental cleaning device [Air-Floss (AF), Philips] (Rmaile et al, 2013;2015;Fabbri et al, 2015). We demonstrated that biofilms exhibited fluid-like behaviour on the order of milliseconds in response (Fabbri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-speed imaging has provided important information on fluid-biofilm-surface interactions and show that although a statistically significant amount of biofilm is removed from the area, the biofilm becomes fluidized and spreads across the surface 17 . The ability of biofilms to become fluidized probably explains the tenacity of bacteria on surfaces after pulsed lavage 18 and may contribute to the low success rate of irrigation and debridement alone in treating periprosthetic infections.…”
Section: Current Therapeutic Approachesmentioning
confidence: 99%
“…and a wider killing zone around the zone of clearance (Appendix Figure 2). The microspray used in our experiments was a turbulent complex twophase burst of water and air which lasted 60 ms (Fabbri et al 2016). Once the spray impacts the surface, the flow can be divided in two regions: an impingement region in the centre of the impact followed by a two-phase wall-jet region where the flow spreads radially outward.…”
mentioning
confidence: 99%